Upaya Pemerintah Tiongkok Melalui Kerjasama Internasional Dalam Menangani Kejahatan Perdagangan Pengantin (Bride Trafficking) - Ayu Puspita Rani; Dr. Dra. Reni Windiani, M.S.; Anjani Tri Fatharini, S.IP., M.A. (Journal of International Relations, 2022)
Bride trafficking is a phenomenon in China where women from outside of China, such as Myanmar, Vietnam, Cambodia, Laos, even Indonesia become the victims of human trafficking to become brides against their will. The traffickers, disguised as marriage brokers lure the victims by promising them a well-paid jobs and better life compared to their life and job at home countries. A question then rises: how is the Chinese’s government effort in tackling bride trafficking? This research seeks to answer how is the Chinese’s government effort in tackling bride trafficking with the theory of International Cooperation. The argument of this research, the efforts done by Chinese’s government are cooperating in bilateral, multilateral and regional levels. The result of this research shows that the efforts taken by Chinese government to tackle bride trafficking are cooperating in bilateral level with Indonesia and Vietnam; acceeded UN Trafficking in Persons Protocol in multilateral level; and signed the MoU with Mekong countries in regional level. This research suggests for the Chinese government to strengthen the cooperations in order to narrow the space for the bride traffickers. Another suggestion, aimed for the future research is to pay more attention on the efforts to save the trafficked brides and their welfare after being released from the trafficking situation. This research uses qualitative research methods and data collection is done through literature study, from books, journals, articles, and websites.